The Role of Activating E2Fs in Neural Stem Cell Maintenance from Development to Adulthood - Gemae, Raghda (Université d'Ottawa / University of Ottawa, 2016)
The recent discovery of adult neural precursor cells (NPCs) in the dentate gyrus and the subventricular zone of the lateral ventricles of most mammals holds much hope for the potential regeneration of damaged brain tissue. However, their use has been limited by their low numbers and relatively quiescent state, particularly in the aging brain. Previous studies from our laboratory have demonstrated a crucial role for the Rb/E2F pathway in the regulation and proliferation of NPCs, and the direct mechanistic involvement of E2F3 in regulating the pluripotency factor, Sox2. More recently, our investigations into the roles of E2F1 and E2F3 in during adult neurogenesis have revealed that loss of both these genes results in a dramatic loss of adult NPCs. Here, we have employed the Emx1-Cre and Nestin-CreERT2 transgenic models, to specifically delete E2F1 and E2F3 in the cerebral cortex and in NPCs in order to investigate the role of both these genes in embryonic neurogenesis. Our results suggest a switch in the requirement for both E2Fs 1 and 3 between embryonic and adult NPCs, demonstrated by a decrease in NPC proliferation and numbers starting only during late embryonic development and persisting through postnatal neurogenesis. These findings suggest that E2Fs 1 and 3 are essential for the maintenance of stem cells and neurogenesis in the adult brain. Moreover, their deletion results in defects in learning and memory. These studies reveal a crucial role for activating E2Fs in the long-term maintenance and proliferation of neural stem cells.
Keywords: Neural Stem Cell; Stem Cell; Neurogenesis; Development; Transcription Factor